Neutron stars colliding with binary companions: formation of hypervelocity stars, pulsar planets, bumpy superluminous supernovae and Thorne–Żytkow objects. Issue 3 (20th October 2022) - Hirai, Ryosuke; Podsiadlowski, Philipp
ABSTRACT: We perform three-dimensional (3D) hydrodynamical simulations of new-born neutron stars (NSs) colliding with main-sequence binary companions after a supernova explosion. Based on those hydrodynamical models, we construct a semi-analytical formula that describes the drag force inside stars with steep density gradients. We then compute the outcome of NS–companion collisions over a wide range of parameters using the semi-analytical formula. Depending on the direction and magnitude of the natal kick, we find that the collision may lead to various outcomes. For relatively fast kicks and high impact parameters, the NS may penetrate the companion star envelope without merging. By allowing the NS to plunge through their companions, the companion can be accelerated to have runaway velocities up to ∼10 per cent above the theoretical upper limit considered in classical binary disruption scenarios. The NS can capture and carry away up to a few per cent of the companion envelope as it escapes, which may form pulsar planets or cause outflows through accretion to heat the ejecta from inside and power the supernova light curve. For lower impact parameters, the NS will directly merge with the companion and form a Thorne–Żytkow object. In intermediate cases, the NS penetrates the companion envelope several times before merging, possibly causing multiple bumps in the supernova light curve like in SN2015bn and SN2019stc.